Comparison of paracetamol and diclofenac prescribing preferences for adults in primary care - Bayram, Dilara; Aydın, Volkan; Şanlı, Abdullah; Abanoz, Mustafa Naci; Sıbıç, Büşra; Pala, Sedat; Ataç, Ömer; Akıcı, Ahmet (Cambridge University Press, 2021)
Introduction: The most frequently prescribed analgesic drugs in primary care centers in Turkey are diclofenac and paracetamol, respectively. In this study, we aimed to compare paracetamol-included prescriptions (PIP) and diclofenac-included prescriptions (DIP) generated for adult patients in primary care. Methods: In this cross-sectional study, PIPs (n = 280 488) and DIPs (n = 337 935) created for adults by systematic sampling among primary care physicians working in Istanbul in 2016 (n = 1431) were examined. The demographic characteristics, diagnoses, and additional drugs in PIPs and DIPs were compared. Results: Women constituted the majority in both groups (69.8% and 67.9%, respectively; P < 0.05), and mean age at PIP (52.6 +/- 18.8 years) was lower compared to DIP (56.3 +/- 16.1 years), (P < 0.05). In single-diagnosis prescriptions, 11 of the 15 most common diagnoses in PIP were respiratory tract infections (47.9%); three pain-related diagnoses formed 4.6% of all these prescriptions. In DIP, the number of pain-related diagnoses, mostly of musculoskeletal origin, was eight (28.5%); four diagnoses (7.8%) were upper respiratory tract infections. While hypertension was the third most common diagnosis in PIP (6.1%), it was ranked first in DIP (8.0%). The percentage of prescriptions with additional analgesic (14.0% versus 18.3%, P < 0.001), proton-pump inhibitor (13.8% versus 18.4%; P < 0.001), and antihypertensive (22.0% versus 24.8%, P < 0.001) was lower in PIP compared to DIP. However, the percentage of prescriptions with antibiotics (31.3% versus 14.7%, P < 0.001) was higher in PIP. Conclusion: Paracetamol appears to be preferred mostly in upper respiratory tract infections compared to the preference of diclofenac rather in painful/inflammatory musculoskeletal conditions. The presence of hypertension among the most commonly encountered diagnoses for these analgesic drugs points to challenges in establishing the diagnosing-treatment match and indicates potential irrational prescribing practice, especially for interactions.
Keywords: Analgesic; Diclofenac; Pain; Paracetamol; Prescribing; Primary Care